Feasibility Study On Wind Power Generation Potential In Peninsular Malaysia - Md Ramli, Siti Solehah (2012)
The wind speed data of year 2005 to 2009 has been analysed at eleven selected locations in Peninsular Malaysia and the data at USM Engineering Campus had been used as a case study. The analytical data shows that the best potential area for wind turbine installation is at Kota Bharu where the annual mean wind speed is found to be around 3.46 m/s at 50m height. The correlation and multiple regression analysis also have been conducted and the results reveal that the pressure, temperature and humidity parameter does not influence the wind speed characteristic in Peninsular Malaysia.